Plant defences on land and in water: why are they so different? - Vermeij, Geerat J. (Ann Bot, 2016)
Background Plants (attached photosynthesizing organisms) are eaten by a wide variety of herbivorous animals. Despite a vast literature on plant defence, contrasting patterns of antiherbivore adaptation among marine, freshwater and land plants have been little noticed, documented or understood. Scope Here I show how the surrounding medium (water or air) affects not only the plants themselves, but also the sensory and locomotor capacities of herbivores and their predators, and I discuss patterns of defence and host specialization of plants and herbivores on land and in water. I analysed the literature on herbivory with special reference to mechanical defences and sensory cues emitted by plants. Spines, hairs, asymmetrically oriented features on plant surfaces, and visual and olfactory signals that confuse or repel herbivores are common in land plants but rare or absent in water-dwelling plants. Small terrestrial herbivores are more often host-specific than their aquatic counterparts. I propose that patterns of selection on terrestrial herbivores and plants differ from those on aquatic species. Land plants must often attract animal dispersers and pollinators that, like their herbivorous counterparts, require sophisticated locomotor and sensory abilities. Plants counter their attractiveness to animal helpers by evolving effective contact defences and long-distance cues that mislead or warn herbivores. The locomotor and sensory world of small aquatic herbivores is more limited. These characteristics result from the lower viscosity and density of air compared with water as well as from limitations on plant physiology and signal transmission in water. Evolutionary innovations have not eliminated the contrasts in the conditions of life between water and land. Conclusion Plant defence can be understood fully when herbivores and their victims are considered in the broader context of other interactions among coexisting species and of the medium in which these interactions occur.